Global warming: preventing irreversibility - Lane, Jan-Erik (2018)
The United Nations Framework Convention on Climate Change meets again in Bonn for the COP23 in the fall with Fiji as host, the focus should be upon the GOAL II in the COP21 Treaty: decarbonisation with 30-40 per cent of 2005 levels until 2030. Several countries now meet the GOAL I of halting the rise in CO2 emissions. And the rest should be asked and helped to do so. But the GOAL II is a very big challenge. It can only be fulfilled with massive investments in solar panel parks. JEL Classification: Q4; Q5.